Human respiratory system: designing student worksheet based on inquiry to promote 21st-century skills - Y Yusnaeni; Angela G Lika; Sriarmila Hiul (Universitas Negeri Jakarta, 2019)
A student worksheet is one of the learning resources containing work intended for students to be more active in learning. A student worksheet is designed based - inquiry so that learning is more meaningful and student-centered. Investigation optimally involves all students' ability to search and investigate systematically, critically, logically, analytically, so that they can formulate their findings confidently. This study aims to produce student worksheet based - Inquiry with profiles and qualities that are feasible to use in classroom learning, developed by adapting the ADDIE model. The validity of the worksheet development results is measured from the result of validation by the expert validator, the quality, and practicality of the worksheet seen from the responses given by students and teachers. The data of the development results were analyzed descriptively qualitatively. The results showed that the worksheet based-Inquiry had fulfilled the three requirements for proper worksheet preparation that is didactic, constructive, and technical requirements. Student worksheet based-Inquiry declared very valid with an average value of 3.70 and is feasible to use. A student worksheet is also in a first category based on the responses of students and teachers with scores of 82.92% and 83.50%, respectively, so it is concluded feasible to be used in learning.